The potential of car sharing for automotive dealers - Greif, Jana Simone (2020)
Shouldcar dealerships includecar sharing in their business model? This question is answered by (i) analyzing the car sharing market, (ii) studying the current opportunities and challenges of car dealers, (iii) conducting a survey ofpotential users of car sharing,and (iv) interviewing automotive industry experts. It is concluded that there is potential for car dealers to integrate car sharing in to their business model. However, various provisos and success factors should be taken into account.